Recent Studies of the North Magnetic Dip Pole - Whitham, K.; Loomer, E.I.; Dawson, E. (ARCTIC, 1959)
Reviews post-war studies on the secular motion of the dip pole and predicts its position for epoch 1960. 0:74.8 ± 0.3 N., 99.6 ± 1.2 W. The daily track during moderate magnetic disturbance approximates an ellipse with a north-south long axis of ca. 30 mi and an east-west axis of ca. 18 mi. Estimated and observed tracks 1600-1950 are mapped, and sources and magnitudes of errors are discussed. The secular motion, as estimated by various methods, averages 5.5 mi/yr to the north and 0.7 mi/yr to the east.